Ambientalismo de livre mercado e análise do discurso ambiental: o caso do Brasil Mata Viva - Godinho, Marcos Vinícius Ferreira de Almeida (2018)
Capitalism and the environmental, for many, are seen as extreme opposites. One of the intentions in this work is to discuss how this conflict is developed and to show solutions for it, having the case of Brasil Mata Viva to represent the realized theoretical discussion. However, it is not central to this work to explore the conflict between capitalism and the environment, but to show a reality where both were put together harmonically. This work has two main theoretical focal points: free market environmentalism and environmental discourse analysis. Firstly, an exposé about free market environmentalism and its main concepts was made, paving the way the theory used to study Brasil Mata Viva. Secondly, the environmental discourse analysis is debated, and is shown its categories. Right after, an presentation of Brasil Mata Viva was realized, showing its history, actions and relations with society. Finally, the data obtained is discussed in the light of the methodologies given by the theories of free market capitalism and environmental discourse analysis where markets, relations with institutional public figures, community and the environment are central. The results show a contradictory combination, although successful, rooted by the studied context which challenges the theorized conceptions.